Efficacy and safety of filgotinib in patients with moderately active rheumatoid arthritis and an inadequate response to methotrexate - Buch, MH; Walker, D; Edwards, CJ; Barry, J; Akroyd, L; Omoruyi, EVE; Taylor, PC (Oxford University Press, 2024)
Objectives: Clinical trials restricted to moderately active RA are limited. Filgotinib is approved for treating moderate to severe active RA. This post hoc analysis assessed efficacy and safety of filgotinib in moderately active RA. Methods: In FINCH 1, patients with active moderate to severe RA and inadequate response to methotrexate received filgotinib 200 mg or 100 mg (FIL200/FIL100) once daily, adalimumab 40 mg every 2 weeks, or placebo, all with methotrexate (n=1,755). This subgroup analysis was conducted in patients with a moderate baseline Disease Activity Score in 28 joints using C-reactive protein (DAS28-CRP; >3.2 to ≤5.1; n=425 [24.2%]). Results: A higher proportion of patients achieved DAS28-CRP <2.6, Clinical Disease Activity Index (CDAI) remission (≤2.8), low disease activity (LDA) (DAS28- CRP ≤3.2 or CDAI ≤10), and American College of Rheumatology (ACR20/50/70) responses with FIL200 and FIL100 versus placebo at Weeks 12 and 24. Week 12 ACR20 response rates (primary endpoint) were 77.9%, 67.8%, and 43.8%, respectively. Approximately 75% of patients achieved DAS28-CRP LDA by Week 24 with either filgotinib dose. FIL200 and FIL100 elicited greater improvements in patient-reported outcomes than placebo. The efficacy of filgotinib, maintained through Week 52, was comparable to that of adalimumab. Frequency of adverse events (AEs) was similar with filgotinib and adalimumab. Infections were the most common AEs; incidence rates were 40–53% in active treatment groups. Conclusion: In this subpopulation with moderately active RA, the efficacy and safety of filgotinib were similar to those in the overall FINCH 1 population (patients with active moderate to severe RA).